AB0229 Fatigue in Rheumatoid Arthritis Patients with Low Disease-Activity. (10th June 2014) - Bode, C.; Lenferink, L.; Nikolaus, S.; Vonkeman, H.
Abstract : Background: Unless effective pharmacological treatment for controlling disease-activity in rheumatoid arthritis, the majority of patients report clinically relevant fatigue which challenges the view of disease-activity as main cause of elevated levels of fatigue. Objectives: The primary aim of this study was to analyse the prevalence of fatigue in RA patients with very low disease-activity, by using a novel multidimensional fatigue questionnaire (BRAF-MDQ). As the Dutch version was not yet validated, the second aim was to psychometrically evaluate the Dutch BRAF-MDQ. Methods: Data of 199 RA patients (69% women, mean age 59 years, mean DAS-28 =1.99) were selected from a multi-centre randomized clinical trial. Firstly, the prevalence rates of clinical important levels of fatigue were examined and Spearman Rho correlations were used to determine how fatigue was related to disease-activity. Secondly, the dimensional structure, internal consistency, discriminant validity, distinctiveness, reliability, construct validity and possible floor- and ceiling effects were examined to psychometrically evaluate the BRAF-MDQ. Results: Clinically relevant fatigue was present in 73% of the patients. The correlation coefficients between disease-activity and dimensions of fatigue ranged from 0.05 to 0.09. The dimensional structure of the BRAF-MDQ was broadly confirmed, but major floor effects were detected. Conclusions: The findings indicate that even though RA inflammation is clinically under control, the majority of the patients still reported clinically relevant fatigue. Not all items of BRAF-MDQ are equally suitable for patients with low disease-activity, pointing to possibilities for improving fatigue measurement by, for example, adaptive testing methodologies. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4619